Keeping lupus patients on hydroxychloroquine during the COVID-19 pandemic - Littlejohn, Emily (Cleveland Clinic Journal of Medicine, 2020)
Hydroxychloroquine (HCQ) is in short supply as a result of the coronavirus disease 2019 (COVID-19) pandemic, presenting a challenge to rheumatologists to ensure their patients with systemic lupus erythematosus (SLE) continue to take this essential drug. HCQ is the only SLE treatment shown to increase survival and any change in the HCQ regimen is potentially dangerous. Changes in the HCQ regimen should be made jointly with the patient after a discussion of the available evidence and expert opinion and the patient’s preferences. Providers need to make thoughtful, informed decisions in this time of medication shortage.